The Reticulospinal Pathway Does Not Increase Its Contribution to the Strength of Contralesional Muscles in Stroke Survivors as Compared to Ipsilesional Side or Healthy Controls - Sheng Li; Sheng Li; Minal Bhadane; Minal Bhadane; Fan Gao; Ping Zhou; Ping Zhou (Frontiers in Neurology, 2017)
ObjectiveStartling acoustic stimulation (SAS), via activation of reticulospinal (RS) pathways, has shown to increase muscle strength in healthy subjects. We hypothesized that, given RS hyperexcitability in stroke survivors, SAS could increase muscle strength in stroke survivors. The objective was to quantify the effect of SAS on maximal and sub-maximal voluntary elbow flexion on the contralesional (impaired) side in stroke survivors as compared to ipsilesional (non-impaired) side and healthy controls.DesignThirteen hemiparetic stroke survivors and 12 healthy subjects volunteered for this investigation. Acoustic stimulation was given at rest, during ballistic maximal and sustained sub-maximal isometric elbow contractions using low (80 dB) and high intensity sound (105 dB). The effect of acoustic stimuli was evaluated from EMG and force recordings.ResultsPrevalence of acoustic startle reflex with shorter latency in the impaired biceps was greater as compared to the response in the non-impaired side of stroke subjects and in healthy subjects. Delivery of SAS resulted in earlier initiation of elbow flexion and greater peak torque in healthy subjects and in stroke subjects with spastic hemiplegia during maximal voluntary elbow flexion tasks. During sub-maximal elbow flexion tasks, SAS-induced force responses were slightly greater on the impaired side than the non-impaired side. However, no statistically significant difference was found in SAS-induced responses between impaired and non-impaired sides at maximal and sub-maximal elbow flexion tasks.ConclusionThe findings suggest RS hyperexcitability in stroke survivors with spastic hemiplegia. The results of similar SAS-induced responses between healthy and stroke subjects indicate that RS projections via acoustic stimulation are not likely to contribute to muscle strength for stroke survivors to a significant extent.